2023
DOI: 10.3390/brainsci13050816
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Tyrosine Phosphatase 1B Inhibitor in Early Brain Injury of Subarachnoid Hemorrhage in Mice

Abstract: Clinically, early brain injury (EBI), which refers to the acute injuries to the whole brain in the phase of the first 72 h following subarachnoid hemorrhage (SAH), is intensely investigated to improve neurological and psychological function. Additionally, it will be meaningful to explore new therapeutic approaches for EBI treatment to improve the prognosis of patients with SAH. To investigate the underlying neuroprotection mechanism in vitro, the Protein tyrosine phosphatase 1B inhibitor (PTP1B-IN-1) was put i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Mouse experiments have shown that stress-induced glial cell boundaries can be formed on the first day after SAH, and pericytes regulate the formation of astrocyte glial boundaries through the EphA4/EphrinB2 signaling pathway, inhibiting inflammatory cell infiltration and improving neurological function [ 72 ]. Protein tyrosine phosphatase 1B inhibitor (PTP1B-in-1) can regulate the IRS-2/AKT signaling pathway, improve neuroinflammation and neuronal apoptosis, and exert neuroprotective functions [ 73 ]. In animal experiments, it was found that takinib alleviates EBI by targeting the inhibition of the TAK1-ROS-NLRP3 inflammasome signaling pathway [ 74 ].…”
Section: Potential Mechanisms Of Early Brain Injurymentioning
confidence: 99%
“…Mouse experiments have shown that stress-induced glial cell boundaries can be formed on the first day after SAH, and pericytes regulate the formation of astrocyte glial boundaries through the EphA4/EphrinB2 signaling pathway, inhibiting inflammatory cell infiltration and improving neurological function [ 72 ]. Protein tyrosine phosphatase 1B inhibitor (PTP1B-in-1) can regulate the IRS-2/AKT signaling pathway, improve neuroinflammation and neuronal apoptosis, and exert neuroprotective functions [ 73 ]. In animal experiments, it was found that takinib alleviates EBI by targeting the inhibition of the TAK1-ROS-NLRP3 inflammasome signaling pathway [ 74 ].…”
Section: Potential Mechanisms Of Early Brain Injurymentioning
confidence: 99%